Gas adsorption on modified zeolite adsorbent - Kamarudin, Khairul Sozana Nor; Chieng, Yu Yuan; Hamdan, Halimaton; Mat, Hanapi (2005)
Various industrial applications involving microporous material lead to synthesis of zeolite with different structural framework and properties. Even though the synthesized zeolite could expand the applications in adsorption processes, some structures are highly hydrophobic or highly hydrophilic, others are thermally unstable at temperature higher than 700 Â°C or adsorb at very low capacity. Therefore, their applications are limited to certain application. Thus, to overcome the problem, modifications or post synthesis treatments are introduced in order to produce modified zeolites with desired properties for specific applications. However, any modification causes some changes, thus special attention has to be paid to the texture of the zeolite because it may result in severe structural defects or variants. This paper will examined the effect of different metal cations on adsorption characteristics. The metal cations were introduced by cation exchange method. It was found that the presence of different metal cations alters the properties of zeolites and thus the adsorption characteristics. Results from gas adsorption uptake and FTIR spectra show that charge and size of metal cations could influence, the gas adsorption capacity and the interaction of gas adsorbates with zeolite surface.